1976
DOI: 10.1111/j.1432-1033.1976.tb10194.x
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Oxidase and Xanthine Dehydrogenase from Wild‐Type Drosophila melanogaster and Immunologically Cross‐Reacting Material from ma‐1 Mutants

Abstract: The pleiotropic effect of the mu-1 mutation on the enzymes xanthine dehydrogenase and aldehyde oxidase in Drosophila melanogaster can most readily be explained by assuming that the enzymes share a subunit or cofactor whose synthesis is controlled by the mu-1 locus. According to this hypothesis a protein or a tightly bound cofactor common to both enzymes should be inactive or missing in the corresponding immunologically cross-reacting material found in ma-1 flies. Three of the proteins involved were purified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 30 publications
(13 reference statements)
1
16
1
Order By: Relevance
“…Thus, crude extracts of the null mutant were active in the NADH assays. However, aldehyde oxidase is fairly readily separated from xanthine dehydrogenase, e.g., by (NH,),SO, fractionation (Andres, 1976), and accordingly, we found no evidence on our peak fractions for the presence of aldehyde oxidase after the stage 111 MonoQ purification step. In more detail, before accepting results of NADH : 2,6-dichloroindophenol or methylene blue oxidoreductase assays at this purification stage, we checked the constancy amongst different fractions across the chromatography peak, of the activities in the NADH: 2,6-dichloroindophenol or methylene blue oxidoreductase assays, relative to xanthine dehydrogenase activity.…”
Section: __contrasting
confidence: 44%
See 1 more Smart Citation
“…Thus, crude extracts of the null mutant were active in the NADH assays. However, aldehyde oxidase is fairly readily separated from xanthine dehydrogenase, e.g., by (NH,),SO, fractionation (Andres, 1976), and accordingly, we found no evidence on our peak fractions for the presence of aldehyde oxidase after the stage 111 MonoQ purification step. In more detail, before accepting results of NADH : 2,6-dichloroindophenol or methylene blue oxidoreductase assays at this purification stage, we checked the constancy amongst different fractions across the chromatography peak, of the activities in the NADH: 2,6-dichloroindophenol or methylene blue oxidoreductase assays, relative to xanthine dehydrogenase activity.…”
Section: __contrasting
confidence: 44%
“…To seek to understand the molecular basis of the modified enzymic properties of the xanthine dehydrogenase variants, we undertook purification studies, though their scope was limited by the quantities of the tlies that could readily be grown. Some earlier purification procedures (Andres, 1976;Edwards et al, 1977) for the Drosophilu enzyme depended on immuno-affinity chromatography, using polyclonal antibodies and requiring potentially damaging conditions for elution of the enzyme. In preference, we developed a new and simplified six-step procedure, as described in Materials and Methods, that depended mainly on chromatography employing FPLC techniques, and applied this to the enzyme from several Drosophila strains.…”
Section: __mentioning
confidence: 99%
“…In Drosophila the ma-1 mutation results in loss of xanthine dehydrogenase, pyridoxal oxidase and aldehyde oxidase activities [19]. Flies carrying the ma-1 mutation have a protein which cross-reacts with native xanthine dehydrogenase, but this cross-reacting material has the same molecular weight as the native xanthine dehydrogenase [18]. Dickison [20] has reported that aldehyde dehydrogenase cross-reacting material in ma-1 flies has a sedimentation constant about half that of the native wildtype enzylme.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the complementation map of ma-1 [21] looks superficially similar to the one of cnxE [22]. However, Andres [18] has found that the cross-reacting material of ma-1 flies contains flavin, iron and molybdenum. Mutation at another gene in Aspergillus, hxB, affects both xanthine dehydrogenase I and I1 activities without affecting the NADH dehydrogenase activity or the subunit structure of the enzymes [4,9,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation